Advancing Sustainability and Green Engineering in Mechanical Engineering Education: Concepts, Research Trends, Challenges, and Implementation Strategies - Meli Fiandini; Gafurdjan Israilovich Mukhamedov; Dustnazar Omonovich Khimmataliev; Asep Bayu Dani Nandiyanto (Bumi Publikasi Nusantara, 2025)
Sustainability and green engineering are increasingly vital in mechanical engineering education as industries prioritize environmental responsibility, energy efficiency, and waste reduction. This study aims to review and synthesize current research trends, challenges, and implementation strategies concerning the integration of sustainability into mechanical engineering curricula. We used a systematic review approach using literature published between 2019 and 2024. Results indicate that although sustainability is recognized as important, its integration remains inconsistent due to curriculum gaps, limited hands-on experiences, weak industry collaboration, and insufficient faculty training. Proposed solutions include project-based learning, interdisciplinary courses, strengthened partnerships with industry, and the incorporation of green technologies such as carbon capture and circular economy practices. These strategies are essential because they bridge the gap between theory and real-world application. The findings highlight the need for standardized educational frameworks and enhanced collaboration. This review contributes to the development of curricula that prepare future engineers to address complex environmental challenges.